Neonatal Cytomegalovirus Infection: The experience of a level III neonatal intensive care unit - Beatriz Morais Pereira Pinto (2021)
Background: Congenital cytomegalovirus (cCMV) is one of the most common congenital infections. Routine screening of pregnant women for CMV infection is currently not recommended. cCMV infection is a health problem with high associated morbidity, since it is often underdiagnosed. This paper aims to report the experience of a level III Neonatal Intensive Care Unit (NICU) on neonatal cytomegalovirus infection. Methods: The authors performed a retrospective observational study on children with suspected cCMV infection at birth, between January 1997 and December 2020. Demographics, laboratory tests on CMV infection, data on pregnancy follow up and neonatal morbidity were collected and analyzed. Results: There were 18 neonates with suspected cCMV infection. The median of maternal age was 31 years (20-41). The median of gestation duration was 37 weeks (26-41 weeks) and the median birthweight of neonates was 2495g (950-3646). cCMV infection was confirmed in 14 (78%) cases. In 5 (28%) neonates, their mothers had seroconversion, 4 (22%) in the first trimester. These women were submitted to amniocentesis and pharmacological treatment. Seven mothers (38.9%) had unknown serological status and the suspicion was raised based on abnormalities on the brain image, fetal growth restriction and other clinical signs. Twelve neonates had clinical signs that could be attributed to cCMV infection. Treatment for cCMV infection was instituted in 8 (57%) of the 14 affected neonates. The median of length stay in the NICU was 14 days (1- 130). Conclusion: Our data are in accordance with those found in the literature, namely in the non- screening of pregnant women and testing only after suspected findings on fetal ultrasound assessment. Since our sample was collected from a NICU, most of neonates had clinical signs or sonographic abnormalities compatible with cCMV. Once cCMV infection can cause late sequels, the implementation of a universal screening would probably be beneficial.